2019
DOI: 10.1186/s12860-019-0217-0
|View full text |Cite
|
Sign up to set email alerts
|

In silico prediction of structural changes in human papillomavirus type 16 (HPV16) E6 oncoprotein and its variants

Abstract: Background HPV16 infection is one of the main risk factors involved in the development of cervical cancer, mainly due to the high oncogenic potential of the viral proteins E6 and E7, which are involved in the different processes of malignant transformation. There is a broad spectrum of intratypical variation of E6, which is reflected in its high diversity, biological behavior, global distribution and risk of causing cervical cancer. Experimental studies have shown that the intratypical variants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…32 nucleotide mutations were detected in HPV68 E6-E7, 16 were novel mutation and 16 were non-synonymous mutations. HPV68 variants were distributed in three clusters, 68.75% variants belong to lineage C., 3 variants (MK874666, MK874661, MK874668) appeared between C and D lineages, indicated that there are many types of HPV infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 nucleotide mutations were detected in HPV68 E6-E7, 16 were novel mutation and 16 were non-synonymous mutations. HPV68 variants were distributed in three clusters, 68.75% variants belong to lineage C., 3 variants (MK874666, MK874661, MK874668) appeared between C and D lineages, indicated that there are many types of HPV infection.…”
Section: Discussionmentioning
confidence: 99%
“…The DNA extraction was performed by Nucleic Acid Extraction Kit (Health Gene Technologies, China), and genotyped by HPV nucleic acid testing and genotyping kit (Health Gene Technologies, China), according to the manufacturer's instructions. The genotyping kit can classify 25 HPV subtypes (6,11,16,18,26,31,33,35,39,42,43,44,45,51,52,53,56,58,59,66,68,73,81,82,83).…”
Section: Genomic Dna Extraction and Hpv Typingmentioning
confidence: 99%
“…Numerous studies have shown that E7 is one major transforming gene of HPV16 [23][24][25][26][27][28]. Therefore, it is the key factor that causes cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, our team has adopted an in-silico analysis approach to evaluate the structural changes of E6 and its variants [28,29]. Since, evidence of the role of the PBM motive of E6 in the progression and aggressiveness of CC has been published [4,26], and the possible changes in the behaviour of the AA variants and the other variants are not clear.…”
Section: Introductionmentioning
confidence: 99%